Sonochemically synthesized microporous metal–organic framework representing unique selectivity for detection of Fe3+ ions. (1st February 2019) - Moradi, Ehsan; Rahimi, Rahmatollah; Safarifard, Vahid
Graphical abstract: In this paper, we report the exploration of highly luminescent three-dimensional microporous metal–organic framework, [Zn2 (oba)2 (bpy)], synthesized by sonochemistry for highly selective and sensitive detection of Fe 3+ in MeOH solution via a fluorescence quenching mechanism. Abstract: Synthesis of metal–organic framework (MOF) materials via ultrasound (US) irradiation involves shorter reaction times and offers enhanced control of particle size and morphology compared to conventional electric heating. Here, we report the exploration of highly luminescent three-dimensional microporous metal–organic framework, [Zn2 (oba)2 (bpy)], (1 ; H2 oba = 4, 4′-oxybis(benzoicacid); bpy = 4, 4′-bipyridine) synthesized by sonochemistry for highly selective and sensitive detection of Fe 3+ in MeOH solution via a fluorescence quenching mechanism. Fluorescence titration experiments reveal that1 is highly selective for Fe 3+ ion with a response time of <2 min and the limit of detection (LOD) reaches a low level of 0.3 μM (17 ppb). The luminescence is completely quenched in 100 µM MeOH solution of Fe 3+ . Furthermore, the static quenching constant is calculated to be upper than 58 000 M −1 by the fluorescence titration experiment in low concentration of Fe 3+ . No interferences from 250 μM As 3+, Cd 2+, Zn 2+, Co 2+, Ni 2+, Cu 2+, Pb 2+, Mn 2+ and Al 3+ were found for the detection of Fe 3+ . Importantly, 1 can be cycled at least four times without loss of emission signals, which suggests that the functionalized1 is a promising luminescent probe for selectively sensing of Fe 3+ ions.